CONSUMPTION OF ULTRA-PROCESSED AND FRESH FOODS AMONG FEDERAL PUBLIC EDUCATION WORKERS: IMPLICATIONS FOR HEALTH PROMOTION (CIPEEX, 2025)
Introduction: The regular consumption of ultra-processed foods has increased and has been linked to negative health outcomes. Conversely, the regular intake of fresh or minimally processed foods has declined. Understanding these dietary patterns is essential for guiding health promotion efforts. Objective: To examine the association between the regular consumption of sweets and healthy foods among employees of the Federal Network for Professional, Scientific, and Technological Education (RFEPCT). Method: This cross-sectional epidemiological study employed a quantitative approach and was carried out in November 2022 after receiving approval from the Research Ethics Committee (protocol number 5,270,596). The sample consisted of 1,563 RFEPCT professionals, including teachers and TAE. Sociodemographic variables and the PeNSE questionnaire were analyzed. Consumption of sweets or healthy foods on ≥5 days per week was considered regular (CR), while consumption on ≤4 days per week was considered irregular (CI). The effect measure used was the prevalence ratio (PR) with 95% confidence intervals (CIs). Results: The PR for sweets was positively associated with being female (p < 0.001), living in the south (p < 0.001), the southeast (p < 0.001), and the midwest (p = 0.003), and holding a teaching position (p = 0.001). It was negatively associated with older age groups: 48 to 60 years (p < 0.001) and 61 to 72 years (p < 0.008). A positive association was also observed with CI for fresh fruit and vegetables (p = 0.010). Conclusion: The associations found suggest that sociodemographic and healthy eating factors influence the consumption of UPF as sweets among RFEPCT employees. These findings highlight the need for interventions that promote healthy eating practices in institutional work environments.
Keywords: food; education workers; ultra-processed food